Photorealistic rendering of knitwear using the lumislice - Xu, Ying-Qing; Chen, Yanyun; Lin, Steve; Zhong, Hua; Wu, Enhua; Guo, Baining; Shum, Harry (SIGGRAPH '01: Proceedings of the 28th annual conference on Computer graphics and interactive techniques, 2001)
We present a method for efficient synthesis of photorealistic free-form knitwear. Our approach is motivated by the observation that a single cross-section of yarn can serve as the basic primitive for modeling entire articles of knitwear. This primitive, called the lumislice, describes radiance from a yarn cross-section based on fine-level interactions — such as occlusion, shadowing, and multiple scattering — among yarn fibers. By representing yarn as a sequence of identical but rotated cross-sections, the lumislice can effectively propagate local microstructure over arbitrary stitch patterns and knitwear shapes. This framework accommodates varying levels of detail and capitalizes on hardware-assisted transparency blending. To further enhance realism, a technique for generating soft shadows from yarn is also introduced.